A slush-like polar structure for high energy storage performance in a Sr0.7Bi0.2TiO3 lead-free relaxor ferroelectric thin film. Issue 13 (4th March 2022) - Luo, Jin; Zhu, Hao; Zheng, Tianyang; Qian, Hao; Liu, Yunfei; Lyu, Yinong
Abstract : A slush-like polar structure with 2–4 nm multi-domains and low-angle domain walls, as the origin of the high energy storage performance in Sr0.7 Bi0.2 TiO3 thin films, is directly visualized and quantitively described. Abstract : Dielectric materials as capacitors with high energy storage performance have received substantial attention for applications as important components in modern electrical and electronic systems. Relaxor ferroelectrics, as one of the popular dielectric materials, have demonstrated extraordinary energy storage performance. However, the origin of this extraordinary performance is not fully understood due to the complex atomic structural heterogeneity. Here, aberration-corrected scanning transmission electron microscopy is employed to study the atomistic structure of a Sr0.7 Bi0.2 TiO3 lead-free relaxor ferroelectric thin film, which shows high energy density of 77.8 J cm −3, good energy efficiency of 67.8%, and high frequency, temperature and antifatigue stability simultaneously. A slush-like polar structure with 2–4 nm multi-domains and low-angle domain walls, rather than polar nanoregions, is observed, revealed and quantitively described in the Sr0.7 Bi0.2 TiO3 relaxor ferroelectric thin film. This slush-like polar structure is considered to enable flexible domain switching under an electric field, and is proposed as the mechanism for the high energy storage performance. These results benefit the understanding of the atomic-scale structure of relaxor ferroelectrics and provide guidance for the exploration of new relaxor ferroelectrics with high energy storage performance.